Simulación en tiempo real de un sistema de alta potencia basado en tecnología VSC-HVDC (2017)
"The use of real-time platforms in this project comes under the academic incentive to develop studies on high power systems based on VSC-HVDC technology that shows a behavior over time. Figure A.2 shows the steps for a real-time simulation. These steps are: Edit, compile, execute and interact. RT-LAB handles everything, including code generation, with an easy-to-use interface. With just a few clicks of the mouse, a Simulink model becomes an interactive real-time simulation application." -- Tomado del Formato de Documento de Grado.